2021
DOI: 10.1016/j.bpj.2021.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric signaling in C-linker and cyclic nucleotide-binding domain of HCN2 channels

Abstract: Opening of hyperpolarization-activated cyclic nucleotide-modulated (HCN) channels is controlled by membrane hyperpolarization and binding of cyclic nucleotides to the tetrameric cyclic nucleotide-binding domain (CNBD), attached to the C-linker disk (CL). Confocal patch-clamp fluorometry revealed a pronounced cooperativity of ligand binding among protomers. However, by which pathways allosteric signal transmission occurs remained elusive. Here, we investigate how changes in the structural dynamics of the CL-CNB… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“…Under these model assumptions, the phenomenon of subunit cooperativity would be confined to the level of the CNBDs. This interpretation gets nice support from recent computational studies on the allosteric signaling within the CNBD and the C-linker of structurally related HCN2 channels [ 38 ]. The authors applied MD simulations and a rigidity-theory-based approach and identified complex interactions to mediate the cAMP effect.…”
Section: Discussionsupporting
confidence: 59%
“…Under these model assumptions, the phenomenon of subunit cooperativity would be confined to the level of the CNBDs. This interpretation gets nice support from recent computational studies on the allosteric signaling within the CNBD and the C-linker of structurally related HCN2 channels [ 38 ]. The authors applied MD simulations and a rigidity-theory-based approach and identified complex interactions to mediate the cAMP effect.…”
Section: Discussionsupporting
confidence: 59%
“…30 Allosteric effects due to ligand binding are described with the free-energy measure Δ G i ,CNA (see ESI eqn (S4)†). 59–61 The per-residue Δ G i ,CNA values from individual trajectories correlate well for each system, indicating robust and consistent results were obtained across the independent MD trajectories (Table S4†). We performed receiver operating characteristic (ROC) analyses to evaluate whether the pockets identified in our MD simulations comprise more residues with larger Δ G i ,CNA values than other surface regions (Fig.…”
Section: Resultsmentioning
confidence: 55%
“…Similar to previous measurements, ligand binding was quantified by the fluorescence intensity of a fluorescent cAMP derivative binding to the channels in the excised patch membrane ( Biskup et al, 2007 ; Kusch et al, 2010 ). As cAMP derivative, 8-AHT-Cy3B-cAMP (f1cAMP) was used ( Otte et al, 2019 ; Pfleger et al, 2021 ), which contains a different dye moiety and a longer linker compared to the originally used cAMP derivative 8-AET-Dy547-cAMP (fcAMP) ( Kusch et al, 2010 ) (see also Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%